2016
DOI: 10.1007/s11274-016-2174-5
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites of endophytic Xylaria species with potential applications in medicine and agriculture

Abstract: Fungal endophytes are important sources of bioactive secondary metabolites. The genus Xylaria Hill (ex Schrank, 1789, Xylariaceae) comprises various endophytic species associated to both vascular and non vascular plants. The secondary metabolites produced by Xylaria species include a variety of volatile and non-volatile compounds. Examples of the former are sesquiterpenoids, esters, and alcohols, among others; and of the latter we find terpenoids, cytochalasins, mellein, alkaloids, polyketides, and aromatic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Xylaria spp., associated with the Azadirachta indica plant from China, are a source of new bioactive compounds, some of which exhibit relevant pharmacological properties for drug discovery [141], presenting with antifungal activities against C. albicans, Aspergillus niger, and Fusarium avenaceum [127,142]. The fungus Mycosphaerella, which is an endophyte of the plant Eugenia bimarginata from Brazil, has been shown to produce two eicosanoid acids that have antifungal activities against C. neoformans and C. gattii [143].…”
Section: Endophytic Fungi In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Xylaria spp., associated with the Azadirachta indica plant from China, are a source of new bioactive compounds, some of which exhibit relevant pharmacological properties for drug discovery [141], presenting with antifungal activities against C. albicans, Aspergillus niger, and Fusarium avenaceum [127,142]. The fungus Mycosphaerella, which is an endophyte of the plant Eugenia bimarginata from Brazil, has been shown to produce two eicosanoid acids that have antifungal activities against C. neoformans and C. gattii [143].…”
Section: Endophytic Fungi In Agriculturementioning
confidence: 99%
“…Basidiomycete fungus [140] Eucalyptus grandis [140] Scleroderma A and B Triterpenoid lanostane [140] Candida albicans C. tropicalis C. grusei C. parapsiosis [140] Xylaria spp. [141] Azadirachta indica [127,142] Bioactive compounds [141] C. albicans Aspergillus niger Fusarium avenaceum [127,142] Mycosphaerella spp. [143] Eugenia bimarginata [143] Eicosanoid acids [143] Cryptococcus neoformans C. gattii [143] Cryptosporiopsis quercina [144] Wood species in Europe [144] Cryptocandin lipopeptide [144] Botrytis cinerea [144] Novel molecular biology approaches have been used for the identification and characterization of genetic elements and metabolites involved in the interactions between plants and endophytic microorganisms [146].…”
Section: Endophytic Fungi Plant Metabolites Antifungal Activitiesmentioning
confidence: 99%
“…Other than the taxonomic report and phylogenetic analysis, there is no report on bioactivity screening in this genus. However, members of xylariaceous fungi are well known to produce diverse secondary metabolites showing various activities such as antimicrobial, antimalarial, cytotoxic and photoprotective activities, and with chemical skeletons such as sesquiterpenoinds, diterpenoids, triterpene glycosides, steroids, alkaloids, aromatic compounds, pyranones and polyketides Kuhnert et al 2015;Macias-Rubalcava and Sanchez-Fernandez 2017;Marciel et al 2018). Therefore, we first screened the culture filtrates of 109 endophytic fungal strains belonging to Xylariaceae for antibacterial activity against two phytopathogens and the selected strain, JS-1675, followed by the isolation and identification of its active compound.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Xylaria Hill ex Schrank comprises more than 300 species, some of which have received special attention due to their potential as sources of novel secondary metabolites. A recent review showed that more than 180 compounds, including sesquiterpenoids, diterpenoids, diterpene glycosides, triterpene glycosides, steroids, N-containing compounds, pyrone derivatives, and polyketides, have been isolated from this genus [20,21]. Specifically, from X. feejeensis, integric acid, xylaropyrone, and the nonenolide xyolide have been isolated.…”
Section: Fungal Endophytes From Hintonia Latifloramentioning
confidence: 99%